Analisis Dan Pengujian Sistem Pada Website Medited Berbasis PHP Menggunakan Standar ISO/IEC 29119 - Dea Amelia; Raihan Pratama; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
This study aims to analyze and test the Medited website built with PHP for the CRUD doctor data module using the international standard ISO/IEC 29119. The testing was conducted to assess system reliability, input validation, and data integrity. The method applied is Black Box Testing, focusing on functional testing without examining the internal code structure. A total of 25 test cases were created to evaluate the Create, Read, Update, and Delete features, including input validation, management of data dependencies, and deletion confirmation mechanisms.The test results show that most basic CRUD features functioned as expected, with 14 test cases passing and 11 test cases failing. Major bugs were found in input validation for Name, Email, and Phone, deletion of data with dependencies, and data display when the table is empty. The analysis indicates that these failures may compromise data integrity and user experience.Based on these results, improvements are recommended for input validation, protection mechanisms for deleting dependent data, addition of Delete All confirmation, and enhancement of user feedback. The application of ISO/IEC 29119 standards proved useful in providing a systematic, well-documented, and repeatable testing framework to improve system quality.